2020
DOI: 10.1177/1420326x20974733
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the thermal plume generated by body heat dissipation on the containment of fume hood

Abstract: The impact of human body heat dissipation on the containment of a fume hood was conducted via experiments and numerical model. The experiments evaluated hood face velocity and the temperature around the mannequin; the results validated the simulation. The numerical model was based on the governing equations of fluid flow via the finite volume method. The face velocities (0.3–0.9 m·s− 1 ) and temperature differences (11°C, 8°C and 5°C) between the surface of the mannequin and its surroundings were used as varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…They reported that changes in the flow field due to changes in the shape of the worker might affect the concentration in the breathing zone. Liu et al 7 also reported CFD analysis to evaluate the containment performance of the fume hood by simulating an upright worker in front of the fume hood, with the human body surface temperature was set at 31°C and the opening surface air velocity was varied from 0.3 to 0.9 m/s. As a result, they found that the performance of the opening surface was affected by the thermal plume caused by the human heat generation when the opening surface air velocity was less than 0.4 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that changes in the flow field due to changes in the shape of the worker might affect the concentration in the breathing zone. Liu et al 7 also reported CFD analysis to evaluate the containment performance of the fume hood by simulating an upright worker in front of the fume hood, with the human body surface temperature was set at 31°C and the opening surface air velocity was varied from 0.3 to 0.9 m/s. As a result, they found that the performance of the opening surface was affected by the thermal plume caused by the human heat generation when the opening surface air velocity was less than 0.4 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…29 Furthermore, the realizable k-ε model has been proven to predict the airflow inside of the hood chamber precisely. 3,18 Obtaining a better agreement would necessitate the use of LES, which however is much more computationally expensive than steady RANS. 29 Therefore, the realizable k-ε model with SIMPLE algorithm was adopted for numerical calculations.…”
Section: Cfd Simulationsmentioning
confidence: 99%
“…Airborne contaminants can linger for long periods of time in the circular eddy current behind the sash and near the doorsill, which can heighten the risk of contaminant leakage. 18 Pressure loss also fell by 30.5% by reducing the recirculation zones inside the hood, thereby limiting the energy consumption of the hood. 19 A planar jet was developed to form a layer of clean air that can reduce the amount of pollutants escaping from the eddy near the doorsill.…”
Section: Introductionmentioning
confidence: 99%